Peaking factors of dry weather flows in Głogów combined sewage system = Współczynnik nierównomierności przepływu pogody bezdeszczowej w kanalizacji ogólnospławnej Głogowa - Nowogoński, Ireneusz; Ogiołda, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the results of dry weather flowrate studies in inflow and outflow channels of overflow structure PB-1. The facility is located in P.Skargi Street in Głogów. Based on the results the average daily peaking factor of dry weather sewage outflow was estimated.
Keywords: kanalizacja ogólnospławna; natężenie przepływu ścieków; współczynnik dobowej nierównomierności; combined sewage system; dry weather flowrate; peaking factor